Attenuation in Spanish: sociolinguistic and dialectal patterns. Towards a map of attenuation in Spanish. - Cestero Mancera, Ana M.ª; Albelda Marco, Marta (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Attenuation is a highly complex pragmatic phenomenon that has become an imperative object of study in recent decades. Over a decade ago, PRESEEA initiated the coordinated research conducted to put together the geolectal and sociolectal map of the attenuation strategy in Spanish.This article presents, comparatively, the most updated results of our research on this socio-pragmatic and geolectal variability in the use of attenuation when engaged in interaction. More concretely, the sociolectal patterns of attenuation in six geolects of Spanish language are collected, as well as the patterns displayed by subjects with higher education in eleven areas. The communities studied are, in Spain, the following: Madrid, Valencia, Santander, Granada, Málaga, Sevilla, and Las Palmas de Gran Canaria. And in Latin America, Santiago de Chile, Barranquilla, Puebla de Zaragoza and Mexico City. The comparison of the use of attenuation in these areas shows trends in each gegraphical area, as well as convergences and divergences between them and feasible changes in progress.
Keywords: PRESEEA; linguistic attenuation; sociopragmatic variation; dialectal variation